Good Global Supply Chain Governance, Corruption, and Welfare: an Empirical Evidence From Indonesia - Khairudin Khairudin; Evi Gantyowati; Jaka Winarna; Nurdiawansyah Nurdiawansyah; Aminah Aminah (International Journal of Supply Chain Management, 2021)
— Social welfare can only be realized if local governments have good global supply chain governance and low corruption. This research aims to prove the effect of good global supply chain governance and corruption on welfare. This research was conducted on all provincial governments in Indonesia in 2014-2018. Good global supply chain governance was measured using the Indonesia Governance Index published by The Partnership for Governance Reform, corruption is measured through corruption cases carried out by public officials in each province published by the KPK-RI (Indonesia's Corruption Eradication Commission), while welfare was measured by the Human Development Index published by BPS-RI (Indonesia’s Central Bureau of Statistics). The analysis was done through multiple regression testing. The results show that (1) the implementation of good global supply chain governance, corruption and social welfare in local governments in Indonesia is still bad; (2) local governments with high human development index and high government index cannot guarantee a low level of corruption; (3) good global supply chain governance is evidence to significantly improve welfare; (4) corruption has actually been shown to significantly improve welfare. This finding proves the importance of good global supply chain governance for local governments to accelerate the improvement of social welfare. Besides, the impact of corruption on welfare in this study is interesting.